Factors Affecting the Acceptance of Dairy Farming Standards by Modernized Farmers for Agricultural Extension in Thailand - Rapankum, Narawut; Hanmontree, Rueangrit; Srilapat, Chanoknan; Niljinda, Kanjanaporn; Chaisombut, Phornphat (Asian Journal of Agriculture and Rural Development, 2022)
Milk production in compliance with dairy farm standards (DFS) assists farmers in improving the quality of local raw milk, facilitating more efficient farm management, and potentially increasing raw milk prices. In addition, it helps consumers to consume milk that is safe for their health. This study aimed to investigate the factors affecting the acceptance of DFS among modernized farmers in Sakon Nakhon and Udon Thani, Thailand. A total of 201 respondents were selected using the cluster sampling method. A structured questionnaire was utilized to collect data. The data were analyzed using binary logistic regression with 12 variables: age, education, experience in dairy farming, types of labor, size of dairy farming land, farm size, amount of raw milk yields, processing cost of raw milk, the profitability of raw milk production, access to and use of information on dairy farming, number of attended dairy farming workshops, and farmer satisfaction towards their dairy cooperative administration. The results indicate that modernized dairy farmers with more experience, medium-sized farms (21-100 dairy cows/farm), combined family and hired labor, and higher raw milk yield were more willing to accept DFS. This result is relevant in the context of agricultural extension according to government policies to raise the quality of raw milk in Thailand.